Structural, Electronic and Optical Properties of CsMI3(M=Ge,Sn,Pb) Perovskite from First Principles - Liu, Haoxuan; Zhang, Haiming (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The all-inorganic lead halide perovskites has received wide attention in optoelectronic applications such as solar cells and light-emitting diodes due to its high photoabsorption, suitable bandgap and good stability. Based on the first principles, the electronic structure and optical properties of the structure are studied by substituting all the lead elements in CsPbI3 with Ge and Sn.We found that the structural stability of all the substituted materials was enhanced. The tolerance factors of CsGeI3 and CsSnI3 were 0.934 and 0.874, respectively. The most important point is to replace the toxic Pb element, which not only reduces environmental pollution but also can be more suitable for commercial production. By analyzing the imaginary part of the dielectric function and absorption coefficient, it is found that the blue shift occurs in all the materials which replace Pb element, and the absorption ability of sun light is stronger in the visible light range, which proves the foundation for lead free perovskite solar cells.